Bentuk Tindakan Seksisme Dalam Kumpulan Cerpen Karya Edogawa Rampo - Fitri Amelia Dewi; Diana Puspitasari; Anggita Stovia (KIRYOKU, 2022)
This research aims to describe the acts of sexism committed by male characters to female characters in a collection of short stories by Edogawa Rampo. The material objects in this research are the short stories of Hakuchuumu, Ningen Isu, and Shinri Shiken. The method used in this research is descriptive qualitative with literature review research method. The theory used in this research is sexism theory by Natasha Walter. The results of this research indicate that there are two acts of sexism, namely 1) sexual violence which includes sexual harassment and sexual objectification, and 2) violence. Based on the results of data analysis, it can be concluded that there are depictions of acts of sexism against women. Based on the results of data analysis, it can be concluded that in the collection of short stories by Edogawa Rampo there are depictions of acts of sexism against women that occur because of gender stereotypes that give rise to a culture of domination that develops in society. The perception of subject-object and superior-inferior in the culture of domination, in which women are considered weak creatures and men are stronger beings, is a factor in the occurrence of violence against women.